A Study of the Role and Impact of Graphics on the Title Sequence of Pre-Revolutionary and Post-Revolutionary Iranian Serials - Baghi, Shima; Zandi, Kiyarash (International Journal of Psychosocial Rehabilitation, 2020)
Graphics and motion graphics have been well established in all types of commercial and non- commercial communications, and today’s world is bound to accept it. Entering these images into the world of cinema is an integral part of it. In recent years, most of its manifestation can be found in the title sequence such that the stages of creating and examining its aesthetics has become an important and independent matter. Until a few decades ago, title sequence was considered as the last and most insignificant part of filmmaking, perhaps at the very last moments of film and serial presentation simply not to be seen as incomplete. It use was only for informing that was devoid of any artistic beauty. However, any research into the impact of graphics on the title sequence can be a significant advantage for filmmakers and designers who can have a distinct advantage over their competitors by providing an identification of their audience behavior and achieve good performance in the field of titration design. This article seeks to answer the question that if we admit that today’s graphic science has undergone significant improvements since its arrival in Iran, can we witness the same progress in the design of title sequence as a graphic-related industry? We reviewed and collected the information and assumptions required for this article through library study, viewing of Iranian serials title sequences, as well as searching for available sources. In this regard, we selected two works of title sequence for study, indicating changes in the construction of serial title sequence in the 50s and present decade. In this way, we can come to a relatively appropriate conclusion on the role and effect of graphics on the beauty of the title sequences of Iranian serials in the aforementioned period. Finally, based on the results, it can be said that today, due to the advent of technology and the advancement of graphic knowledge, for various reasons, there has not been a much better growth than ever before in the application of graphic science in titration.